Valley Farm exhibit to open with ribbon cutting at Fresno Chaffee Zoo - Hughes, Eddie::::::::: (2013)
The Jordan College of Agricultural Sciences and Technology at Fresno State partnered with Fresno Chaffee Zoo and other Central Valley organizations to create a new zoo exhibit, Valley Farm.